Strengthening Pancasila Student Profiles in the Dimension of Global Diversity Through a Multicultural Education Approach - Maula Devina Yahya; Balqis Najma Negara; Purnomo Purnomo; Naely Azkiya Ramadhani (Tafkir: Interdisciplinary Journal of Islamic Education, 2026)
The persistence of intolerance and discrimination in schools remains a serious challenge to creating an inclusive and harmonious learning environment. Although Indonesia upholds the value of Bhinneka Tunggal Ika, cases of social intolerance continue to occur, showing that tolerance and respect for diversity have not been fully internalized in education. Therefore, multicultural education plays a crucial role in strengthening the global diversity dimension within the Pancasila Student Profile (P5) under the Merdeka Curriculum.  This study aims to analyze the role of multicultural education in the Pancasila Student Profile Reinforcement Project (P5) in developing students’ tolerance, empathy, and openness toward cultural diversity. The research was conducted at SMK Negeri 1 Salatiga using a qualitative case study approach. Data were collected through observation, in-depth interviews, and documentation, then analyzed using Miles and Huberman’s interactive model.  The findings show that integrating multicultural education into P5 effectively shapes students’ respect for differences, cross-cultural awareness, and collaborative communication skills. Moreover, it supports the formation of an inclusive school culture aligned with Pancasila values. The study implies that strengthening multicultural-based character education through curriculum development and teacher training is essential for nurturing globally minded, tolerant, and socially responsible students in the era of globalization.